Ex 12.1

Ex 12.1, 1

Ex 12.1, 2

Ex 12.1, 3

Ex 12.1, 4 Important

Ex 12.1, 5

Ex 12.1, 6 Important

Ex 12.1, 7

Ex 12.1, 8 Important

Ex 12.1, 9

Ex 12.1,10 Important

Ex 12.1, 11

Ex 12.1, 12

Ex 12.1, 13

Ex 12.1, 14 Important

Ex 12.1, 15 Important

Ex 12.1, 16

Ex 12.1, 17 Important

Ex 12.1, 18

Ex 12.1, 19 Important

Ex 12.1, 20

Ex 12.1, 21 Important

Ex 12.1, 22 Important

Ex 12.1, 23 You are here

Ex 12.1, 24

Ex 12.1, 25 Important

Ex 12.1, 26

Ex 12.1, 27

Ex 12.1, 28 Important

Ex 12.1, 29

Ex 12.1, 30 Important

Ex 12.1, 31

Ex 12.1, 32 Important

Last updated at May 7, 2024 by Teachoo

Ex 12.1, 23 (Method 1) Find lim┬(x→0) f(x) and lim┬(x→1) f(x), where f(x) = {█(2x+3.@3(x+1),)┤ ■8(x ≤0@x>0) Finding limit at x = 0 lim┬(x→0) f(x) = lim┬(〖x→0〗^− ) f(x) =lim┬(〖x→0〗^+ ) f(x) ∴ (𝒍𝒊𝒎)┬(𝐱→𝟎) f(x) = 3 (𝒍𝒊𝒎)┬(〖𝐱→𝟎〗^− ) f(x) = lim┬(x→0) (2x + 3) = 2(0) + 3 = 0 + 3 = 3 (𝒍𝒊𝒎)┬(〖𝐱→𝟎〗^+ ) f(x) = lim┬(x→0) 3(x + 1) = 3(0 + 1) = 3(1) = 3 Finding limit at x = 1 "f(x) = " {█(2x+3.@3(x+1),)┤" " ■8(x ≤0@x>0) For x > 0, the function is same Therefore, (𝒍𝒊𝒎)┬(𝒙 → 𝟏) " f(x) " " = " lim┬(x→1) " 3(x + 1) " " = 3(1 + 1)" " = 3 (2)" " = 6" (𝐥𝐢𝐦)┬(𝐱→𝟏) f(x) = 6 Ex 12.1, 23 (Method 2) Find lim┬(x→0) f(x) and lim┬(x→1) f(x), where f(x) = {█(2x+3.@3(x+1),)┤ ■8(x ≤0@x>0) Finding limit at x = 0 lim┬(x→0) f(x) = lim┬(〖x→0〗^− ) f(x) =lim┬(〖x→0〗^+ ) f(x) LHL at x → 0 lim┬(x→0^− ) f(x) = lim┬(h→0) f(0 − h) = lim┬(h→0) f(−h) = lim┬(h→0) 2(–h) + 3 = 2(0) + 3 = 3 RHL at x → 0 lim┬(x→0^+ ) f(x) = lim┬(h→0) f(0 + h) = lim┬(h→0) f(h) = lim┬(h→0) 3(h + 1) = 3(0 + 1) = 3 ∴ (𝒍𝒊𝒎)┬(𝐱→𝟎) f(x) = 3 Finding limit at x = 1 "f(x) = " {█(2x+3.@3(x+1),)┤" " ■8(x ≤0@x>0) For x > 0, the function is same Therefore, (𝒍𝒊𝒎)┬(𝒙 → 𝟏) " f(x) " " = " lim┬(x→1) " 3(x + 1) " " = 3(1 + 1)" " = 3 (2)" " = 6" (𝐥𝐢𝐦)┬(𝐱→𝟏) f(x) = 6